The appropriateness of alternative dispute resolution (ADR) in individual employment disputes: a comparative study of Turkey and the UK - Nalbant, Mustafa (2024)
This thesis is a comparative study of Alternative Dispute Resolution (ADR) in individual employment disputes in Turkey and the UK. It aims to analyse and draw comparisons between these two countries, which have different levels of compulsion in ADR legislative frameworks. The International Labour Organisation (ILO)’s effective dispute resolution criteria are used as comparison benchmarks, with discussion focused on whether, and if so, to what extent ADR methods in Turkey and the UK complied with the criteria as international standards. It argues that the underlying reasons for employing the criteria as yardsticks are not only that they consider the sui generis structure of employment disputes but also that enhancing access to justice through an appropriate resolution of employment disputes forms an integral part of the ILO’s core mission.